Evaluating the TSENCYDENT Routine: A Comprehensive Analysis of Students’ Perceptions on Learning Environment, Speaking Fluency, and Confidence in an Indonesian EFL Context - Beniario; Erlinda Syam; Rini Hendrita (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2026)
Speaking anxiety and limited feedback opportunities in large classes pose significant challenges to developing English speaking fluency in Indonesian high school contexts. This study evaluates students’ perceptions of the Tsencydent routine, a brief, structured warm-up activity designed to address these issues. Employing a convergent mixed-methods design, data were collected via questionnaires and open-ended responses from 20 students at a Muhammadiyah senior high school in Padang Panjang and analyzed using descriptive statistics and thematic analysis. Findings indicate that students generally perceived the routine as useful in fostering a low-pressure learning environment, which appeared to reduce anxiety and increase comfort compared to formal speaking assessments. Commonly reported benefits included perceived growth in vocabulary, improved speaking fluency, and greater self-confidence, often attributed to immediate and constructive teacher feedback. Most students recommended the routine’s continued use. Based on these findings, the study proposes that the Tsencydent routine may serve as a practical pedagogical approach that combines affective support with scaffolded language practice, presenting a possible framework for EFL classrooms facing similar constraints.